2017
DOI: 10.1002/anie.201705452
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Interconversion between 2,5‐Dimethylpyrazine and 2,5‐Dimethylpiperazine by Iridium‐Catalyzed Hydrogenation/Dehydrogenation for Efficient Hydrogen Storage

Abstract: A new hydrogen storage system based on the hydrogenation and dehydrogenation of nitrogen heterocyclic compounds, employing a single iridium catalyst, has been developed. Efficient hydrogen storage using relatively small amounts of solvent compared with previous systems was achieved by this new system. Reversible transformations between 2,5-dimethylpyrazine and 2,5-dimethylpiperazine, accompanied by the uptake and release of three equivalents of hydrogen, could be repeated almost quantitatively at least four ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 37 publications
1
71
0
Order By: Relevance
“…Thereafter, we succeeded in developing a hydrogen-storage system based on the reversible conversion between 2,5dimethylpiperazine and 2,5-dimethylpyrazine using catalyst 6 (eq 10). 22 In this system, in addition to achieving hydrogenation at a comparatively low pressure (15 atm), the main feature was that no solvent was required (or only a very small amount of solvent was used). Reversible and repetitive reactions accompanied by the uptake and release of three equivalents of hydrogen, could be repeated almost quantitatively at least four times without any loss of efficiency.…”
Section: Hydrogen Storage Systems Based On Reversible Interconversionmentioning
confidence: 99%
“…Thereafter, we succeeded in developing a hydrogen-storage system based on the reversible conversion between 2,5dimethylpiperazine and 2,5-dimethylpyrazine using catalyst 6 (eq 10). 22 In this system, in addition to achieving hydrogenation at a comparatively low pressure (15 atm), the main feature was that no solvent was required (or only a very small amount of solvent was used). Reversible and repetitive reactions accompanied by the uptake and release of three equivalents of hydrogen, could be repeated almost quantitatively at least four times without any loss of efficiency.…”
Section: Hydrogen Storage Systems Based On Reversible Interconversionmentioning
confidence: 99%
“…On the basis of our previous studies, in which Cp* iridium complexes exhibited excellent catalytic activity [36][37][38][39][40][41][42][43][44][45][46][47], we attempted to modify one methyl group in the Cp* ligand to hydrogen, ethyl, isopropyl, and t-butyl groups in order to improve the catalytic properties (Scheme 2). A series of cyclopentadienyl-ligated iridium dichloride dimers 1a-1e were synthesized by the reaction of iridium trichloride with parent cyclopentadiene derivatives [62][63][64].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that the dehydrogenation of a cyclic amine, which leads to aromatized N-heterocycles, is also catalyzed by the same iridium complex used for the dehydrogenation of alcoholic substrates [45][46][47]. Hence, we also examined the catalytic activity of a series of iridium complexes (3) in the dehydrogenation of 2-methyl-1,2,3,4-tetrahydroquinoline (10) as a model substrate (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To lower the endothermicity, LOHCs systems based on nitrogen-containing organic hydrides 24 , e.g., N-heterocycles, were developed. These have high H 2 capacities, in the range 5.3-7.3 wt% [31][32][33][34][35][36][37] . These systems can be promoted by various homogeneous and heterogeneous catalysts [38][39][40] under relatively mild conditions ( Fig.…”
mentioning
confidence: 99%